2000
DOI: 10.1016/s0895-7061(00)00253-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between salt sensitivity and target organ damage in essential hypertension

Abstract: Cardiovascular events occur more frequently in sodium-sensitive patients with essential hypertension; recently, sodium sensitivity was shown to be a cardiovascular risk factor independently of other classic factors such as blood pressure and cigarette smoking This study examined the relationship between salt sensitivity status and target organ damage in hypertensive patients. Ninety-six patients (35 men, 61 women) with moderate essential hypertension were studied for salt sensitivity status and the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 34 publications
7
48
0
Order By: Relevance
“…11,12,[29][30][31][32][33] Establishing the genes involved in the BP reactivity to salt would help in identifying patients who would benefit from salt restriction, as well as in preventing salt-sensitive hypertension, a condition known to be associated with increased risk for cardiovascular events. [34][35][36][37][38] In this study, we demonstrated that women with the T allele were more salt sensitive than those without the polymorphism. Interestingly, such an association was not found in men.…”
Section: Nad(p)h Polymorphisms Cardiovascular Risk Factors and Cardisupporting
confidence: 49%
“…11,12,[29][30][31][32][33] Establishing the genes involved in the BP reactivity to salt would help in identifying patients who would benefit from salt restriction, as well as in preventing salt-sensitive hypertension, a condition known to be associated with increased risk for cardiovascular events. [34][35][36][37][38] In this study, we demonstrated that women with the T allele were more salt sensitive than those without the polymorphism. Interestingly, such an association was not found in men.…”
Section: Nad(p)h Polymorphisms Cardiovascular Risk Factors and Cardisupporting
confidence: 49%
“…[7][8][9] Exaggerated BP reactivity to salt, known as salt sensitivity, is associated with increased risk for cardiovascular events. [10][11][12][13][14] Although genetic and acquired factors play a role in the pathogenesis of salt sensitivity, its aetiology is unknown. Older age and insulin resistance have been reported to be associated with salt sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Although the pathogenesis of salt sensitivity is unknown, both genetic and environmental factors appear to interact to determine the exaggerated BP response to changes in salt intake. [6][7][8][9][10][11][12][13][14][15] Increased reactivity of BP to salt is commonly observed in subjects with obesity and associated cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%